(untitled) (Research, Society and Development, 2022)
Objective: to describe the main elements associated with the physical and mental stress of professional nurses in the COVID-19 pandemic. Method: This is an integrative literature review, a method that consists of synthesizing and investigating research results, developed from a bibliographic survey, through scientific articles. The searches were carried out in the following databases: SCIELO, PUBMED and BVS, using the following descriptors, Mental Health, COVID-19, Nursing and Emotional Suffering employing. The descriptors were combined using the Boolean operators "AND" and "OR". Results: Nurses were directly impacted by the COVID-19 pandemic, causing work overload, increase in the number of patients infected with the virus, separation from their families, anxiety attacks, stress, insomnia, emotional exhaustion, professional dissatisfaction, symptoms of depression, fear, and poor salary conditions. Final considerations: In summary, a special attention to the class is essential, since it is undervalued and demands better working conditions and salaries. The attention to mental health is also fundamental so that they can perform their activities with satisfaction and quality, since many professionals were removed due to psychological disorders.